Analisis Daya Dukung Lahan Pertanian (Sawah) Berdasarkan Hasil Produksi di Kecamatan Waeapo Kabupaten Buru - Buton, La Jati (Jurnal Ecosolum, 2020)
As the population continues to increase in an area, land requirements will also increase. The consequence will be that the population pressure on agricultural land is quite large and will ultimately reduce the output of agricultural production in the region. If this is allowed to continue it is not impossible that the production is not proportional to the food needs of the population. Thus it will cause the carrying capacity of agricultural land to be smaller.The purpose of this study is to analyze the effect of the carrying capacity of agricultural land (rice fields) on production results in Waeapo District, Buru Regency. The research method used was survey research with quantitative descriptive methods. Quantitative descriptive is an activity that is directed to measure or explain carefully certain phenomena or symptoms that are intended to test the truth in the field. The results showed that there were 3 (three) villages namely Savanajaya Village, Waetele Village and Waenetat Village whose carrying capacity of agricultural land (paddy) experienced a deficit (exceeded), while 3 (three) other villages namely Waekerta Village, Waekasar Village and Desa Wanareja carrying capacity of agricultural land has a surplus (sufficient). Thus there is a balance between land needs and the ability of land to provide food (especially rice) to meet the needs of residents in Waeapo District